The Effect of Business Intelligence on Firm Performance Considering the Mediating Role of Knowledge Sharing, Organizational Innovation and Competitive Advantage - Hossein Norouzi; Soheila Khoddami; Zahra Abidi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study analyzes the effect of business intelligence on firm performance by considering the mediating role of knowledge sharing, organizational innovation, and competitive advantage.Methodology: This study is descriptive correlational research. The statistical population of the research is small and medium entrepreneurs in Tehran province. The method of data collection is a questionnaire. The number of items in the questionnaire is 42, the sample size is 202 questionnaires, and all have been completed correctly. Structural equation modelling and SPSS and PLS 3 software were used to analyze the data.Findings: Findings indicate that business intelligence impacts competitive knowledge sharing and firm performance, showing that managers should focus on implementing business intelligence to enhance their performance and increase their ability to respond to external risks and challenges. The findings also show that knowledge sharing impacts competitive advantage, and finally, competitive advantage impacts firm performance.Originality/Value: The study showed that business intelligence in the organization and small and medium entrepreneurs will increase performance, competitive advantage, and knowledge sharing. This research can help organizations to use business intelligence in their activities in a more specialized way.